PEMANFAATAN TANAMAN OBAT SEBAGAI TRADISI BEBUBUS DI DESA PRINGGASELA NUSA TENGGARA BARAT - Nurvazila Virdaus; Munawir Sazali (Bioscientiae, 2026)
This study examines the use of medicinal plants in the bebubus tradition of the Sasak community in Pringgasela Village, East Lombok. The aim of this study is to understand the utilisation and ethnobotanical role of medicinal plants. This study employs a qualitative descriptive approach to understand, describe and analyse aspects of the traditional bebubus culture. Data collection was carried out in April 2025 through interviews with belian (elders) and residents of Pringgasela, followed by analysis using thematic analysis based on the Miles & Huberman model, involving data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Bebubus tradition remains preserved and is passed down through the generations. The main ingredients used in the Bubus-making process include galangal (Kaempferia galanga), fennel (Foeniculum vulgare), rice (Oryza sativa), fenugreek (Trigonella foenum-graecum), champaca flowers (Magnolia champaca), ylang-ylang flowers (Cananga odorata), and edelweiss (Anaphalis javanica). The people of Pringgasela believe in the efficacy of Bebubus in treating various health issues such as fever in children, denggong, tiwang (itching), and amar ghaib (disturbances caused by supernatural beings).